Mean curvature effect on the response and failure of round-hole tubes submitted to cyclic bending - Kuo-Long Lee (SAGE Publishing, 2021)
This paper presents an experiment and analysis to investigate the response and failure of 6061-T6 aluminum alloy round-hole tubes with different hole diameters of 2, 4, 6, 8, and 10 mm subjected to cyclic bending at different curvature ratios of −1.0, −0.5, 0.0, and +0.5. The curvature ratio is defined as the minimum curvature divides by the maximum curvature. Four different curvature ratios are employed to highlight the mean curvature effect. It can be seen from the experimental results that the moment-curvature relationships gradually relax and become steady states after a few bending cycles for curvature ratios of −0.5, 0.0, and +0.5. The ovalization-curvature relationship depicts an asymmetrical, ratchetting and increasing as the number of bending cycles increases for all curvature ratios. In addition, for each hole diameter, the relationships between the curvature range and the number of bending cycles necessary to initiate failure on double logarithmic coordinates display four almost-parallel straight lines for four different curvature ratios. Finally, this paper introduces an empirical formula to simulate the above relationships. By comparing with experimental results, the analysis can reasonably describe the experimental results.